1958
DOI: 10.1002/pol.1958.1202711519
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic viscosities of cellulose derivatives

Abstract: Intrinsic viscosities of cellulose acetates of degrees of substitution 2.86 and 3.00 and of cellulose trinitrate have been investigated as functions of temperature, solvent, and molecular weight. Large negative temperature coefficients (ca. −0.6% per degree) of [η] appear to be characteristic of cellulosic chains. These observed decreases in [η] with temperature are due to increases in chain flexibility, which are reflected in decreases in the characteristic ratio r 02/M. The rather large variations in [η] wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

1959
1959
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 15 publications
5
24
0
1
Order By: Relevance
“…Moreover, since both HPC and HPMC have rigid chains due to the chemical nature of cellulosic polymers (glucose unit), their solutions exhibit nonideal solution behavior as noted by Flory 14. Therefore, they have different water absorption characteristics 15–17…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since both HPC and HPMC have rigid chains due to the chemical nature of cellulosic polymers (glucose unit), their solutions exhibit nonideal solution behavior as noted by Flory 14. Therefore, they have different water absorption characteristics 15–17…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the parameter K is independent of molecular weight. This may not be the case for stiff chain polymers (24,25) for which the draining effect is also important.…”
Section: Cases In Which the Draining Effect Cannot Be Ignored A) Polymentioning
confidence: 90%
“…Dependence of the viscosity on solvent has been noted for cellulose derivatives at higher DP levels [34] but a more striking effect is the decrease of viscosity with temperature, a property of cellulose which is unique among polymers. Flory, et al [34] have shown that the effect of both solvent and temperature on the viscosity of cellulose derivatives is due to a decrease in stiffness, a reduction in the ratio R2/DP, because of alteration in the potential restricting rotation about the glycosidic bond. A freely rotating polymer, on the other hand, expands by long range excluded volume effects and by attractive forces of the solvent for the chain as a whole.…”
Section: Solvent Effects On the Intrinsic Viscositymentioning
confidence: 98%